2015
DOI: 10.1186/s12931-015-0265-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired survival of regulatory T cells in pulmonary sarcoidosis

Abstract: BackgroundImpaired regulatory T cell (Treg) function is thought to contribute to ongoing inflammatory responses in sarcoidosis, but underlying mechanisms remain unclear. Moreover, it is not known if increased apoptotic susceptibility of Tregs may contribute to an impaired immunosuppressive function in sarcoidosis. Therefore, the aim of this study is to analyze proportions, phenotype, survival, and apoptotic susceptibility of Tregs in sarcoidosis.MethodsPatients with pulmonary sarcoidosis (n = 58) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 36 publications
7
38
1
Order By: Relevance
“…In addition to enhanced TNF-TNFR2 stimulation, which we suggest here, there might be additional mechanisms accounting for the observed elevation in T reg levels. One of these mechanisms include an apoptosis defect, as described recently by Broos et al [7].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to enhanced TNF-TNFR2 stimulation, which we suggest here, there might be additional mechanisms accounting for the observed elevation in T reg levels. One of these mechanisms include an apoptosis defect, as described recently by Broos et al [7].…”
Section: Discussionmentioning
confidence: 96%
“…In cross-over experiments, however, it was shown subsequently that these T regs are incompetent and cannot inhibit the secretion of interferon (IFN)-g and TNF by T effs [5,6]. Furthermore, it was shown that sarcoidosis T regs showed impaired survival compared to healthy controls [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Tregs obtained from pulmonary sarcoidosis patients suffered from impaired survival and increased apoptosis. 67 Moreover, restoration of Treg function was associated with disease remission. 48 Taflin and colleagues have suggested that Tregs may be able to prevent sarcoidosis development, but cannot reverse the granuloma process.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…B lymphocytes may also be involved in sarcoidal granuloma formation, as Lofgren syndrome patients exhibit higher levels of Proprionibacterium acnes-specific IgA antibodies [77]. In chronic diseases, sarcoid T-reg fails to efficiently suppress proliferation and cytokine production by T helper cells [78], and with accumulation of Th1/Th17 cells, further support stabilization of granulomas and chronic disease progression [35]. In contrast, highly plastic and qualified effector T-cells aiming at clearance of the antigens from the granulomas leads to recovery [35,76].…”
Section: Discussionmentioning
confidence: 99%